Matrix Metalloproteinases; A Biomarker of Disease Activity and Prognosis in Spondyloarthritis: A Narrative Review - Slouma, Maroua; Bouzid, Sirine; Dhahri, Rim; Rahmouni, Safa; Litaiem, Noureddine; Gharsallah, Imen; Metoui, Leila; Louzir, Bassem (Current Reviews in Clinical and Experimental Pharmacology, 2023)
Background: Matrix metalloproteinases, as components of the proteolytic system, are deemed to be implicated in the pathogenesis and progression of several rheumatic diseases. Their role in spondyloarthritis has been investigated by several studies. Objective: This article aims to review and summarize the current knowledge related to metalloproteinases in patients with spondyloarthritis. Methods: To examine the association between matrix metalloproteinases and spondyloarthritis, we conducted a narrative review using a literature search in SCOPUS for English-language sources. The search included studies published from the database inception to December 2020. Results: A total number of 74 articles were included. It was found that levels of matrix metalloproteinases 3 were higher in radiographic axial spondyloarthritis patients and seemed to play a role in the progression of joint damage. The levels of matrix metalloproteinases 1, 2, and 9 were upregulated in psoriatic arthritis patients compared to psoriasis and could identify psoriasis patients who would develop rheumatic manifestations. The levels of matrix metalloproteinases correlated significantly with disease activity in ankylosing spondylitis and decreased upon treatment with Tumor Necrosis Factor inhibitors (TNFi). Conclusion: Excessive matrix metalloproteinases activity is associated with articular destruction. Their levels can reflect disease activity, structural damage, and response to TNFi in patients with spondyloarthritis. Nevertheless, further studies are needed to confirm these results.
Keywords: matrix metalloproteinases